Hydrogen thermal reductive Cu nanowires in low temperature Cu–Cu bonding. (13th June 2017) - Du, Li; Shi, Tielin; Su, Lei; Tang, Zirong; Liao, Guanglan
Abstract: Nanostructures have attracted great interest in interconnect applications. Herein, we present a novel low temperature, template-less method for directly preparing Cu nanowires through a hydrogen thermal decomposition-reduction route of Cu(OH)2 → CuO → Cu. The thermal treatments are performed at relatively low temperatures of 180 °C–200 °C to meet the low thermal budget in the semiconductor industry. Cu(OH)2 nanowires are completely transformed into Cu nanowires and the morphologies of the nanowires are successfully preserved without shrinkage of volume and size. Sintering of Cu nanowires occurs at a low temperature of 400 °C in Ar ambient and 350 °C in H2 ambient, respectively. Based on this phenomenon, we innovatively apply the as-synthesized Cu nanowires in Cu–Cu bonding at 150 °C–400 °C. The bonded samples exhibit high shear strengths where Cu nanowires have transformed into Cu nanoparticles, mainly attributed to the enhanced atom diffusion with the existence of nanowires. The present work demonstrates the feasibility of hydrogen thermal reductive Cu nanowires in low temperature Cu–Cu bonding.